Human Mesenchymal Stem Cells Impact Th17 and Th1 Responses Through a Prostaglandin E2 and Myeloid‐Dependent Mechanism. (11th July 2016) - Rozenberg, Ayal; Rezk, Ayman; Boivin, Marie-Noëlle; Darlington, Peter J.; Nyirenda, Mukanthu; Li, Rui; Jalili, Farzaneh; Winer, Raz; Artsy, Elinor A.; Uccelli, Antonio; Reese, Jane S.; Planchon, Sarah M.; et al.
Abstract : A novel prostaglandin E2‐dependent and myeloid cell‐mediated mechanism by which human mesenchymal stem cells (MSCs) can reciprocally induce human Th17 while suppressing Th1 responses has implications for the use of, as well as monitoring of, MSCs as a potential therapeutic for patients with multiple sclerosis and other immune‐mediated diseases. Abstract : Acknowledgements: Human mesenchymal stem cells (hMSCs) are being increasingly pursued as potential therapies for immune‐mediated conditions, including multiple sclerosis. Although they can suppress human Th1 responses, they reportedly can reciprocally enhance human Th17 responses. Here, we investigated the mechanisms underlying the capacity of hMSCs to modulate human Th1 and Th17 responses. Human adult bone marrow‐derived MSCs were isolated, and their purity and differentiation capacity were confirmed. Human venous peripheral blood mononuclear cells (PBMC) were activated, alone, together with hMSC, or in the presence of hMSC‐derived supernatants (sups). Cytokine expression by CD4+ T‐cell subsets (intracellular staining by fluorescence‐activated cell sorting) and secreted cytokines (enzyme‐linked immunosorbent assay) were then quantified. The contribution of prostaglandin E2 (PGE2) as well as of myeloid cells to the hMSC‐mediated regulation of T‐cell responses was investigated by selective depletion of PGE2 from the hMSC sups (anti‐PGE2 beads) and by the selective removal of CD14+ cells from the PBMC (magnetic‐activated cell sorting separation). Human MSC‐secreted products could reciprocally induce interleukin‐17 expression while decreasing interferon‐γ expression by human CD4+ T cells, both in coculture and through soluble products. Pre‐exposure of hMSCs to IL‐1β accentuated their capacity to reciprocally regulate Th1 and Th17 responses. Human MSCs secreted high levels of PGE2, which correlated with their capacity to regulate the T‐cell responses. Selective removal of PGE2 from the hMSC supernatants abrogated the impact of hMSC on the T cells. Selective removal of CD14+ cells from the PBMCs also limited the capacity of hMSC‐secreted PGE2 to affect T‐cell responses. Our discovery of a novel PGE2‐dependent and myeloid cell‐mediated mechanism by which human MSCs can reciprocally induce human Th17 while suppressing Th1 responses has implications for the use of, as well as monitoring of, MSCs as a potential therapeutic for patients with multiple sclerosis and other immune‐mediated diseases. Although animal studies have generated a growing interest in the anti‐inflammatory potential of mesenchymal stem cells (MSCs) for the treatment of autoimmune diseases, MSCs possess the capacity to both limit and promote immune responses. Yet relatively little is known about human‐MSC modulation of human disease‐implicated T‐cell responses, or the mechanisms underlying such modulation. The current study reveals a novel prostaglandin E2‐dependent and myeloid cell‐mediated mechanism by which human MSCs can reciprocally regulate human Th17 and Th1 responses, with implications for the use of MSCs as a potential therapeutic for patients with multiple sclerosis and other immune‐mediated diseases.